Listeriosis After Transient Infectious or Mechanical Disturbance of the Gastrointestinal Tract. Issue 1 (January 2015) - Jacob, Jerry; Lorber, Bennett
<x xml:space="preserve">Abstract</x> Abstract In rare instances, Listeria monocytogenes bacteremia and central nervous system infection appear to have followed either infectious or mechanical disturbances of the gastrointestinal tract. We report a patient who developed postoperative colitis due to Clostridium difficile that in turn was complicated by bacteremia due to L. monocytogenes. To our knowledge, this is the first report of this association. In addition, we summarize other published instances in which invasive listeriosis closely followed gastrointestinal tract disturbances by other infectious agents or endoscopic instrumentation.